Nilai Sosial Dalam Al-Qur'an (Perspektif M. Quraish Shihab Surah Al-Hujurat Ayat 9-13) - Ach. Iqbal Hamdany Abd Hamid (IAIN Madura, 2021)
Abstract Al-Qur'an as a comprehensive holy book applies to every space and time that is bestowed by Allah SWT, to mankind. It contains a lot of values ​​and a very broad message about social behavior. The problems that occur in social life will certainly never end. For this reason, the Qur'an is present as the best solution by providing guidelines for life and guidance on social behavior. This study reveals the social values ​​contained in QS. Al-H ujura> t verses 9-13 and How is the relevance of social values ​​in QS. Al-H ujura> t verses 9-13 with the present life. The approach used is a qualitative approach with the type of library research (library research). The primary data source is Tafsif Al-Misbah only. Based on the results of this study, it can be concluded that the social values ​​contained in surah Al-Hujura>t verses 9-13 are telling mankind to create brotherhood, peace, justice, human unity and mutual respect and prohibiting all actions that can lead to disputes or disunity. can damage the order of relations between fellow human beings in society. Keywords : Value, Social, Al-H ujura> t, M. Quraish Shihab",